The Short-Chain Fatty Acid Acetate in Body Weight Control and Insulin Sensitivity - González Hernández, Manuel A. (Nutrients, 2019)
The interplay of gut microbiota, host metabolism, and metabolic health has gained increased attention. Gut microbiota may play a regulatory role in gastrointestinal health, substrate metabolism, and peripheral tissues including adipose tissue, skeletal muscle, liver, and pancreas via its metabolites short-chain fatty acids (SCFA). Animal and human data demonstrated that, in particular, acetate beneficially affects host energy and substrate metabolism via secretion of the gut hormones like glucagon-like peptide-1 and peptide YY, which, thereby, affects appetite, via a reduction in whole-body lipolysis, systemic pro-inflammatory cytokine levels, and via an increase in energy expenditure and fat oxidation. Thus, potential therapies to increase gut microbial fermentation and acetate production have been under vigorous scientific scrutiny. In this review, the relevance of the colonically and systemically most abundant SCFA acetate and its effects on the previously mentioned tissues will be discussed in relation to body weight control and glucose homeostasis. We discuss in detail the differential effects of oral acetate administration (vinegar intake), colonic acetate infusions, acetogenic fiber, and acetogenic probiotic administrations as approaches to combat obesity and comorbidities. Notably, human data are scarce, which highlights the necessity for further human research to investigate acetate’s role in host physiology, metabolic, and cardiovascular health.